Will women be women?: analyzing the gender difference among financial experts - Daniela Beckmann; Lukas Menkhoff (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
There are robust gender differences in the domains of risk taking, overconfidence and competition behavior. However, as expertise tends to level these differences, we ask whether financial experts still show gender dissimilarities in their domains of decision making? We analyze survey responses of 649 fund managers in the U.S., Germany, Italy and Thailand, and find that female fund managers tend to behave as expected from gender studies: they are more risk averse and shy away from competition in the tournament scenario. The expected lower degree of overconfidence by women is yet so small that it becomes insignificant in fund management.
Keywords: J16; G23; D8; 330; fund managers; gender differences; risk; overconfidence; tournament behavior; Finanzanalysten; Investmentfonds; Führungskräfte; Weibliche Führungskräfte; Geschlecht; Anlageverhalten; Vergleich; USA; Deutschland; Italien; Thailand